Vegetative diversity and arborial indexes of schools in Uruçuí, Piauí: diagnosis and intervention (Research, Society and Development, 2020)
Urbanization rates have been increasing in recent years, with an equally significant population growth, increasing people's distance from vegetated areas. The objective was to analyze the afforestation indexes of public schools of Basic Education in Uruçuí-PI. Previous visits were made to know the internal spaces of these institutions, as well as a qualitative and quantitative survey of their tree indexes, through the projections of the tree indexes of the 03 (three) researched educational institutions, where it was possible to register 167 trees, distributed in 14 species and 10 botanical families, 64% of which are native species in terms of biodiversity. However, in terms of population, 52% are exotic individuals. The study showed low rates in the U.E. José Patrício Franco, requiring actions that aim to correct the current situation. However, this institution does not have enough spaces to implement afforestation, which requires alternative measures. On the other hand, the most satisfactory results for these indexes were registered at Campus Uruçuí. In this sense, the U.E. Cícero Coelho was selected for this intervention. Thus, it is expected that the planting work will contribute to achieving better afforestation rates.